(untitled) (Research, Society and Development, 2022)
The Community Health Agent (CHA) is essential for the satisfactory performance of Comprehensive Health Care. Primary Health Care is the gateway to the community in the health system, which is the scenario in which the ACS work. Regarding child labor, these professionals have the duty to guide, notify and act directly against this harmful situation to the health and development of the child. Objective: This research sought to identify the knowledge of these CHAs about matter child labor. Methodology: a questionnaire was applied in 4 Basic Health Units in the D’água district in the city of Belém-Pará-Brazil. Result: There is a lack of training on child labor in 86.7% of ACS. This was the first University extension practice in the place about child labor that contributed to the gain of knowledge about the realization of notification by the ACS. Conclusion: In this way, an instrument that enables the learned of CHA on such matter is training, in which the University was important for this diagnosis and its incentive to eradicate child labor.